COMPARATIVE EVALUATION OF THE ANTIHYPERTENSIVE EFFECT OF PERINDOPRIL AND LOSARTAN POTASSIUM IN PATIENTS WITH ARTERIAL HYPERTENSION AND STENOTIC CORONARY ATHEROSCLEROSIS BEFORE REVASCULARIZATION: AN OPEN RANDOMIZED COMPARATIVE STUDY - O. A. Osipova; N. N. Kurbakov; A. G. Ovsyannikov; M. A. Vlasenko (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare effects of perindopril and losartan potassium on the parameters of the ambulatory blood pressure (BP) monitoring (ABPM) and circadian BP profile in patients with arterial hypertension (HT) and stenotic coronary atherosclerosis before myocardium revascularization. Material and methods. 59 patients with HT degree 2-3 at the age of 35-69 were examined. ABPM was performed in all patients. Daily profile was assessed by the degree of nocturnal BP reduction. Patients were randomized to receive perindopril or losartan potassium. Perindopril was administered at dose of 4 mg/day with subsequent rising up to 8 mg/day in next 7 days. The initial dose of losartan potassium was 25 mg with subsequent rising up to 50 mg 2 times a day. Duration of observation was 8 weeks. Results. Perindopril reduced 24-hour and daytime systolic BP (SBP) by 17.2% (p<0.0001), nighttime SBP - by 22.5% (p<0.0001), 24-hour and daytime diastolic BP (DBP) - by 18.3% and 17.6% (p<0.0001), respectively , nighttime DBP - by 27.2% (p<0.0001). Losartan potassium reduced 24-hour SBP by 25.7% (p<0.0001), daytime SBP - by 23.6% (p<0.0001), night-time SBP – by 25.5% (p<0.0001), 24-hour DBP - by 27.4%, daytime DBP - by 26.3%, nighttime DBP - by 18.5% (p=0.003). Perindopril decreased in number of non-dippers by 24,3% and night-peakers by 5.4% as well as increased in number of dippers by 27% and over-dippers by 2.7%. A number of patients with SAD profile corresponding to non-dipper type was 45.5% more in losartan taking than this when perindopril receiving (p=0.027). Conclusion. In patients with HT and stenotic coronary atherosclerosis perindopril therapy increases a number of patients with normal BP profile before myocardium revascularization.